Optical properties of all-solid microstructured optical fibers - Uminska, Ada Agnieszka; Grabka, Michał; Pustelny, Szymon; Buczyński, Ryszard; Kujawa, Ireneusz; Gawlik, Wojciech (Photonics Letters of Poland, 2012)
In this Letter, we study optical properties of all-solid microstructured optical fiber made of soft glass. Such fibers have various interesting features including good geometrical stability, low fundamental transmission losses, high Kerr nonlinearity, and large solubility of rare-earth ions. By investigating transmission mechanism, mode structure, and numerical aperture of the fibers and confronting the results with theoretical calculations we demonstrate that the fibers have optical properties similar to those observed in air-silica microstructured optical fibers. This makes the all-solid soft-glass microstructured fibers very attractive for many potential applications. Full Text: PDF References J. R. Hayes, J. C. Flanagan, T. M. Monro, D. J. Richardson, P. Grunewald, and R. Allott, "Square core jecketed air-clad fiber", Optics Express, 14(22):10345-10350, 2006 CrossRef N. A. Issa, "High numerical aperture in multimode microstructured optical fibers", Applied Optics, 43(33):6191-6197, 2004 CrossRef M. Antkowiak, R. Kotynski, T. Nasilowski, P. Lesiak, J. Wojcik, W. Urbanczyk, F. Berghmans, and H. Thienpont, "Phase and group modal birefringence of triple-defect photonic crystal fibres", Journal of Optics A: Pure and Applied Optics, 7(12):763, 2005 CrossRef W. Reeves, J. Knight, P. St. Russell, and P. Roberts, "Demonstration of ultra-flattened dispersion in photonic crystal fibers", Optics Express, 10(14):609-613, 2002 CrossRef C. Martelli, J. Canning, B. Gibson, and S. Huntington, "Bend loss in structured optical fibres", Optics Express, 15(26):17639-17644, 2007 CrossRef T. A. Birks, J. C. Knight, and P. St. Russell, "Endlessly single-mode photonic crystal fiber", Optics Letters, 22(13):961-963, 1997 CrossRef L. Rindorf, J. B. Jensen, M. Dufva, L. H. Pedersen, P. E. Hoiby, and O. Bang, "Photonic crystal fiber long-period gratings for biochemical sensing", Optics Express, 14(18):8224-8231, 2006 CrossRef R. Buczynski, D. Pysz, I. Kujawa, J. Korzeniowski, T. Martynkien. F. Berghmans, H. Thienpont, and R. Stepien, "Supercontinuum generation with microstructured fibers made of soft glass", Photonics Letters of Poland, 1(3):109-111, 2009 CrossRef M. Nielsen, C. Jacobsen, N. Mortensen, J. Folkenberg, and H. Simonsen, "Low-loss photonic crystal fibers for transmission systems and their dispersion properties", Optics Express, 12(7):1372-1376, 2004 CrossRef W. Wadsworth, R. Percival, G. Bouwmans, J. Knight, and P. Russell, "High power air-clad photonic crystal fibre laser", Optics Express, 11(1):48-53, 2003 CrossRef X. Feng, T. M. Monro, P. Petropoulos, V. Finazzi. and D. Hewak, "Solid microstructured optical fiber", Optics Express, 11(18):2225-2230, 2003 CrossRef R. Buczynski, I. Kujawa, R. Kasztelanic, D. Pysz, K. Borzycki, F. Berghmans, H. Thienpond, and R. Stepien, "Supercontinuum generation in all-solid photonic crystal fiber with low index core", Laser Physics, 22(4):784-790, 2012 CrossRef M. Grabka, S. Pustelny, P. Mergo, and W. Gawlik, "Application of continuous wavelet transform for determination of fiber birefringence", Optics Express, 20(13):13878-13885, 2012 CrossRef M. Grabka, B. Wajnchold, S. Pustelny, W. Gawlik, K. Skorupski, and P. Mergo, "Experimental and theoretical study of light propagation in suspended-core optical fibre", Acta Physica Polonica A, 118(6):1127-1132, 2010 DirectLink M. J. F. Digonnet, Hyang Kyun Kim, G. S. Kino, and Shanhui Fan, "Understanding Air-Core Photonic-Bandgap Fibers: Analogy to Conventional Fibers", Journal of Lightwave Technology, 23(12):4169-4177, 2005 CrossRef H. Ebendorff-Heidepriem, R. G. Moore, T. M. Monro, "Progress in the fabrication of the next-generation soft glass microstructured optical fibers", AIP Conference Proceedings, 1055(1):95-98, 2008 CrossRef